Composiciones musicales para los cortos : Nataraja, Trisom-virus fem, Preterición subliminal & Bajo el agua (2020)
This document corresponds to the written section that supports the oral support of the Undergraduate Composition Project for Film and Media. In this way, this document is an exposition of the composition process and the description of synchronized music. In addition, scores of the compositions are attached for the purpose of an authorship registration exercise, but are not intended to serve as a live performance tool. Having said the above, it should be noted that in particular, the purpose of this writing is to explain in a general way the technical and aesthetic compositional process, as well as the dramaturgical and methodological decisions made in the composition throughout the semester. At the beginning of the project, when choosing the subject of the degree work, I was inspired by my constant interest throughout the career, by audiovisual narratives that implicitly and explicitly incorporate questions about movement, the body and its expression. For this reason, the audiovisual material on which I worked finally resulted in the union of four independent projects of corporal and visual expression. Although they do not build a joint linear narrative, they did hope to satisfy some concerns and desires for expression through the creation of musical compositions that were inspired and nourished by visual and bodily discourse.